Application of Ethics in Small Enterprises: An Empirical Study on Dhaka City in Bangladesh - Haque, Ahasanul; Rahman, Sabbir; Azam, Ferdous (Prabandhan: Indian Journal of Management, 2011)
This research has identified that the small organizations of Bangladesh have very little or no interest in the presence and implementation of business ethics. In some areas, they are ethical and in some areas they are not. Despite this type of mixed attitude towards business ethics, it can be said from the findings that in time, ethical trend will change in small organizations as it did in larger organizations. In this study, the consideration and future trend of business ethics are studied using fifty small organizations in Dhaka city in Bangladesh. Results indicate that small organizations demonstrate little or no interest in business ethics. However, their assumptions about the future trend of business ethics are enthusiastic. The study also implies that the status of business ethics in small organizations is not very satisfactory but promising and in the near future, small organizations are likely to comply with business ethics in their organizational activities. This article attempts to find out the current status of ethics and ethical standards in small organizations, especially in Dhaka city in Bangladesh.